SKIN SURFACE + BONE/FRAME, Design through Metaphor and Scale - Spanbroek, Nancy; Doney, R. (IATED, 2011)
The design studio is the heart of Interior Architecture education. It is the spring board for future designers and is the main forum for creative exploration, critical thinking, discussion, development and reflection. Our future designers need to be disciplined, analytical yet flexible thinkers, who are able to address and resolve new and complex problems. This paper reviews the progression and development of an experimental design studio over three years. The studio was established to gauge students' design understanding through drawing and modelling, thereby providing a common tool for discussion. This process raised a number of concerns relating to their understanding of scale, detail and human occupation. Therefore the studio approach was revised to incorporate full-scale sectional models constructed from light-weight materials. The students were inspired to build on their knowledge and creative thinking abilities through a series of explorative exercises and modelling. They thus achieved a greater understanding of scale, detail and design tectonics. The learning experience of students undertaking this studio was enabled and guided by teachers experienced in both university teaching and creative practice, as strategic teaching is central to the creative development process. Through an exploration of the evolving studio process, this paper will show the effectiveness of a pedagogical approach that enables students to bring ideas to life by combining drawing and modelling with full-scale three-dimensional design models. This approach and practice enables students to develop their strengths as designers, as they inhabit their designs and appreciate the human scale.